Фінансові результати діяльності підприємства: визначення, класифікація, управління - Мелень, Олена Валентинівна; Полтавець, Олена Володимирівна (НТУ "ХПІ", 2017)
Усвідомлення суті фінансових результатів роботи підприємств і застосування дієвих управлінських висновків щодо майбутнього їх розвитку є ключовим посилом збільшення ефективності роботи компаній. Одним із провідних питань, стосовно організації обліку фінансових результатів у господарської діяльності, є їх класифікація. Ефективність роботи підприємства значною мірою залежить від якості управлінських рішень відповідно отриманих фінансових результатів діяльності.

In the conditions of economic formation of economic entities, the issue of determining, accounting and management of financial results is the most important in the implementation of economic activities of enterprises, since the financial result is the main summary and the enterprise most precisely determines its economic space and provides an idea of the formation of its financial potential. Awareness of the essence of financial performance of enterprises and the application of effective managerial findings on the future of their development is a key contributor to increasing the efficiency of companies. One of the key issues regarding the organization of accounting for financial results in economic activities is their classification. The efficiency of the enterprise depends to a large extent on the quality of managerial decisions, respectively, on the financial performance gained. A key factor in managing the financial results of an enterprise is the choice of management method, namely: profit planning; profit distribution; profit management based on the organization of liability centers; factor analysis of profit.
Financial results of the business of the enterprise: definition, classification, management
Keywords: прибуток; збиток; бухгалтерський облік; інноваційний процес; управління витратами; financial results; performance; profit; loss